Pelatihan Penyusunan Potensi Investasi Kabupaten Kapuas - Zulfauzan, Ricky; Hartanto, Theo Jhoni; Nugroho, Piter Joko; Putra, Kharisma Nugraha; rahman, rahman; Hutahaean, Saulim DT; Panjika, Yunus Praja (Kahayan : Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to enhance the capacity of local government officials in systematically compiling the investment potential of Kapuas Regency based on data-driven analysis. The training was conducted on 27 November 2025 at the DPMPTSP Hall of Kapuas Regency using a participatory and capacity-building approach. The activity consisted of material preparation, theoretical sessions on investment potentials and opportunities, interactive discussions, a workshop on drafting investment potential documents, mentoring, and evaluation. The results indicate an improvement in participants’ understanding of investment concepts, techniques for identifying priority sectors, and standards for preparing investment potential documents in accordance with the guidelines of the Ministry of Investment/BKPM. Participants were able to produce initial drafts of sectoral investment potentials covering aspects of location, resources, infrastructure, value-added opportunities, and market prospects. The final evaluation shows that the training effectively strengthened the analytical and technical skills of local officials and supported the government’s efforts to provide more accurate, communicative, and competitive investment information.